Mismatch induced speciation in Salmonella: model and data. - Falush, D; Torpdahl, M; Didelot, X; Conrad, D; Wilson, D; Achtman, M (2006)
In bacteria, DNA sequence mismatches act as a barrier to recombination between distantly related organisms and can potentially promote the cohesion of species. We have performed computer simulations which show that the homology dependence of recombination can cause de novo speciation in a neutrally evolving population once a critical population size has been exceeded. Our model can explain the patterns of divergence and genetic exchange observed in the genus Salmonella, without invoking either natural selection or geographical population subdivision. If this model was validated, based on extensive sequence data, it would imply that the named subspecies of Salmonella enterica correspond to good biological species, making species boundaries objective. However, multilocus sequence typing data, analysed using several conventional tools, provide a misleading impression of relationships within S. enterica subspecies enterica and do not provide the resolution to establish whether new species are presently being formed.